Antibacterial activity in three Chaetoceros microalgae species cultures by using antibiotics - Tapia-Gallardo, Yira D.; del Río-Portilla, Miguel A.; Molina-Cárdenas, Ceres A.; Sánchez-Saavedra, M. del Pilar (Revista de Biología Marina y Oceanografía, 2021)
Diatoms, such as Chaetoceros, grow in a mutualistic relationship with bacteria. However, in some cases, it is necessary to grow them in bacteria-free cultures. To reduce bacterial load, antibiotics are used, and on certain occasions it is necessary to use a mixture with more than one antibiotic. This work aimed to obtain a quick and effective protocol to reduce the bacterial load and evaluate the response of three Chaetoceros species with aquacultural importance. Single and mix antibiotics were used. Microalgal and bacterial growth was measured. The growth parameters for diatoms showed that the significantly highest cell concentration was for C. muelleri (3.15 x106 cells mL-1) and the lowest values to C. calcitrans (2.98 x106 cells mL-1). The significantly highest growth rate was for C. calcitrans (0.77 divisions per day), and the lowest values for Chaetoceros sp. (0.60 divisions per day). The growth parameters for heterotrophic bacteria showed that the significantly highest bacterial load was for Chaetoceros sp. (19.16 x106 CFU (Colony-Forming Units) mL-1) and the lowest values were for C. calcitrans (12.23 x106 CFU mL-1). The growth rate of the heterotrophic bacteria present in Chaetoceros cultures was similar among the three studied species. Streptomycin® and sulfate G41® produced a partial reduction of bacterial load. The most effective treatment for all three species was the use of an antibiotic mix composed of ampicillin® (250 μg mL-1), kanamycin® (200 μg mL-1), neomycin® (50 μg mL-1), and streptomycin® (100 μg mL-1) for three days. The mix prepared with the highest antibiotic concentration produced a reduction of bacteria (100%) for three days; however, it also induced a significant reduction of the growth of the three Chaetoceros species.